Faktor-faktor yang Mempengaruhi Desain Akustik Ruang Kelas di Sumatera Utara: Bahasa Indonesia sebagai Bahasa Pengantar Pengajaran - Siregar, Hajizah Azmi (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2026)
Classrooms with optimal acoustic design can directly improve students' listening. Studies have shown that providing a good communication environment for classroom instructors is crucial for students to achieve good grades. Some students who receive poor grades find it difficult to concentrate when speech intelligibility is inadequate or because of excessive noise. However, these studies are based on English as the teaching medium. Indonesia is a developing country with a global population ranking number 4. The Indonesian Ministry of Education anticipates more educational facilities to be built under its mission to realize relevant education of high quality, equitable and sustainable, supported by infrastructure and technology. Will education with Indonesian as the primary language also follow the classroom architecture and acoustics design element? Thus, this study aims to explore views from the relevant important classroom architecture and acoustics design elements. Classroom facilities can support the educating and instructing process. Acoustic factors in the classroom can affect students' and instructors' concentration and comfort. A questionnaire was distributed among Indonesian respondents who work as acoustic engineers, architects, and educators to gain their views about classroom acoustics design factors. Thirty individuals responded to the questionnaire – ten persons in each group. The importance of the acoustics design aspects from each occupation group was measured through statistical analysis of questionnaire results. According to acoustic engineers, Reverberation Times and Sound Insulation are essential to designing classroom acoustics. The architect group assessed Reverberation Times as a less important aspect. However, according to architects and educators, Speech Intelligibility is regarded as the most crucial factor in an Indonesian-language classroom. In short, an evaluation of Indonesian classroom architectural and acoustics features are conducted to make improvements. The school education board, architects, and acoustic engineers could use the results to make better design decisions.